Tyrosine kinase inhibitors re-treatment beyond progression: choice and challenge - Zhang, Ru; Tu, Lingli; Sun, Lan (Journal of Thoracic Disease, 2014)
Tyrosine kinase inhibitors (TKIs) are highly effective agents for the treatment of lung cancer which harbors activated gene mutation. However, for patients with failure of TKI, TKI re-treatment beyond progression (TRBP) is still a potential option that has been proven by many literatures. In this review, we summarize the clinical evidence of TRBP and discuss the potential mechanisms to overcome TKI-acquired resistance.